The historical and social role of fortresses: Sharjah model Fort (1823-2023) - Alshamsi, Badreyya (Al-Adab Journal, 2025)
Forts and castles, as well as towers, served as lines of Defense for the places where they were established. the UAE embraces many castles and fortresses of castles, forts and historical buildings rooted in the depths of local history. castles and fortresses over the centuries served as strongholds and residences for the rulers and leaders of the region. they were also played a distinctive role in determining the history of peoples. the inhabitants of the region have been used to constructing forts and castles since the Umm Al Nar period, which flourished in the Emirates during the third millennium BC. Influential tribal leaders resided in fortified castles that oversaw the region, and also provided protection to the surrounding areas.  The study aimed to identify the most important forts and castles in the UAE and the historical and social and highlighting the role of the historical and social fort of Sharjah during the past 200, years   the study relied on the historical approach to study the subject. The study came out with the most important results: castles and fortresses are spread all over the United Arab Emirates, in every city and village there is a fort and a castle.